Continental‐wide prioritization of protected areas to address global and habitat‐specific goals for avian biodiversity conservation - Yanjie Xu; Diego Pavón‐Jordán; Tyler Hallman; Tristan R. M. Bakx; Lluís Brotons; Sergi Herrando; Alison Johnston; Brett K. Sandercock; Thomas Sattler; Alaaeldin Soultan; Vitalie Ajder; Dawn E. Balmer; et al. (Conservation Biology, 2026)
The United Nations and European Union have set ambitious conservation goals to halt and reverse declines in biodiversity by protecting 30% of land and sea areas by 2030. Effective conservation planning requires evidence‐based spatial prioritization to maximize the coverage of species within designated protected areas. Based on a pan‐European database for occurrence and abundance of breeding birds collected in the 2010s, we applied the Zonation algorithm to identify key areas that would maximize the protection of ranges and populations for 435 species of breeding birds across Europe using either continental or national prioritization targets. When 30% of Europe's highest priority terrestrial areas were selected by the algorithm, 49% of species’ ranges and 63% of species’ populations were protected. When 10% and 30% of the highest priority lands were selected, compared with prioritization using occurrence data, prioritization using abundance data resulted in a higher percentage of species’ populations, especially rare and range‐restricted species, being represented for protected area coverage. Stratifying prioritization by habitat criteria greatly enhanced habitat‐specific conservation efficiency, enabling coverage of over 80% of breeding bird species’ populations in tundra, Mediterranean, and coastal habitats with a selection of 10% of the highest priority areas for each. Our prioritization supports international targets adopted under the Kunming–Montreal Global Biodiversity Framework by identifying key areas and providing a roadmap to guide optimal site protection and conservation planning in Europe.